Effect of pressure pain threshold in fibromyalgia syndrome and rheumatoid arthritis patients - Vijayadas; R. Arun Kaushik; M.S. Roopakala; S. Chandrashekara (Al Ameen Journal of Medical Sciences, 2013)
Background: Pain is an unpleasant sensation signaling tissue damage. Objective measurement of pain helps in devising treatment strategies and relieving patients from sufferings. Objective: The present study was undertaken to evaluate pressure pain threshold in normal subjects, patients with fibromyalgia and rheumatoid arthritis by using algometer. Further to assess severity of pain perception by using visual analog scale. Methods: Measurement was done on 18 tender point sites [TePs] according to ACR criteria on 20 Fibromyalgia [FMS] patients, 20 Rheumatoid arthritis [RA] patients, and 40 healthy normal control [HNC] subjects. The pressure pain threshold [PPT] and Visual analog scale [VAS] were recorded in each TePs. Results: The range of PPT was 0.62 to 3.43 kg/cm2, 0.30 to 3.90 kg/cm2 and 1.41 to 5.35 kg/cm2 and VAS score range was 52.90 to 67.60 mm, 30.5 to 49.00 mm and 23.65 to 41.83 mm in FMS, RA and HNC respectively. Conclusion: There is a significant reduction of PPT in both FMS and RA patients compared to HNC subjects. The VAS score was significantly higher in FMS suggesting altered cognitive response to pain.